Biosorption of Eriochrome black T (EBT) Onto Waste Tea Powder: Equilibrium and Kinetic Studies - Khaled Muftah Elsherif; Ashraf El-Hashani; Kahled Edbey; Farah Alfaqih; Mariam Alomammy; Salima Alomammy (To Chemistry Journal, 2018)
Biosorption of EBT molecules from aqueous solutions onto waste Tea powder (WTP) have been examined in a batch biosorption process. The biosorption procedure was found to be dependent on biosorbent dose, pH of solution, initial dye concentration, and contact time. The experimental equilibrium biosorption data were inspected by Langmuir, Freundlich, Temkin and Dubinin ̶ Radushkevic isotherms models. The Langmuir model gave the best fit by higher correlation coefficient (R2 = 0.997, it assumes as monolayer adsorption). The maximum biosorption capacities determined from the Langmuir isotherm model was 111.11 mg/g, at optimum circumstances. The kinetic studies showed that the biosorption operation of the EBT dye obeyed well pseudo-second-order model. According to the determined biosorption capacity, waste tea powder is considered to be as an effective, low cost, and environmentally friendly biosorbent for the removal of EBT dye from aqueous solutions.